PENDEKATAN ERGONOMI TOTAL PADA AKTIVITAS PRAKTIKUM LAPANGAN DI DAERAH PANAS MENURUNKAN KELELAHAN DAN SUHU INTI TUBUH MAHASISWA - Rolles Nixon Palilingan; Nyoman Adiputra (Bumi Lestari Journal of Environment, 2010)
n the Environmental Physics concentration, to implement the academic curriculum of Physics Department of FMIPA UNIMA, it had been made guidance in the book form to be used in performing the field practicum activity. The guidance had been utilized since the year 2001. However, the conventional activity apparently caused unfavorable risks to the students based on the efficiency of circulatory system so that the students could not attain the intended performance yet. Therefore, it has been arranged a new model of activity with several treatments by using the totally ergonomics approach. In order to test the capability of the activity compared with the conventional one, it had been done a research with the hypothesis: the intervention with the totally ergonomics approach decreases and the body core temperature of the student in the low land/hot area. This research was done by using the design of treatment by subject. The research has used 15 subjects as sample. The measurements of dependent variable were done in the beginning, among units of practicum, and the last on the end of period. The results of the research showed that the activity with the totally ergonomic approach could decrease fatigue and the body core temperature of the student significantly (p<0.05). With the decreasing of fatigue and body core temperature, it means that the activity is good biomechanically and thermally (in low land/hot area). The fatique and hyperthermia condition were responsible as the main cause of the low performance of the students. The activity with ergonomic intervention by using the totally ergonpomics approach succeeds in overcoming the fatigue and hyperthermia condition so that the performance of the students could increase considerably. Based on the research it can be concluded that the intervention with the totally ergonomic approach can: decrease fatigue and decrease body core temperature of the students in doing the field practicum activity. It can be suggested that in doing the activity with ergonomic intervention by using the totally ergonomic approach, principal requisites of every treatment must be fulfilled in order to achieve the intended goals.